Synthesis Of PEG-Coated, Ultrasmall, Manganese-Doped Iron Oxide Nanoparticles With High Relaxivity For T1/T2 Dual-Contrast Magnetic Resonance Imaging - Xiao S (Dove Medical Press, 2019)
Shilin Xiao, Xian Yu, Liang Zhang, Ya Zhang, Weijie Fan, Tao Sun, Chunyu Zhou, Yun Liu, Yiding Liu, Mingfu Gong, Dong Zhang Department of Radiology, Xinqiao Hospital, Army Medical University, Chongqing, People’s Republic of ChinaCorrespondence: Mingfu Gong; Dong ZhangDepartment of Radiology, Xinqiao Hospital, Army Medical University, Xinqiao Street, Shapingba District, Chongqing, People’s Republic of ChinaTel +86 23 6876 3843Fax +86 23 6875 5306Email hummer198625@163.com; hszhangd@163.comBackground: Beyond magnetic resonance imaging (MRI), which has been widely used clinically, molecular MRI (mMRI) can further provide qualitative and quantitative information at the cellular and molecular levels. However, the diagnostic accuracy may not be satisfactory via single-contrast mMRI due to some interferences in vivo. T1/T2 dual-contrast MRI using the same contrast agent (CA) could significantly improve the detection accuracy. Therefore, in this study, we fabricated poly(ethylene glycol) (PEG)-coated, manganese-doped iron oxide nanocomposites (Mn-IONPs@PEG) as T1/T2 dual-contrast CA, and evaluated its feasibility of T1/T2 dual-contrast MRI in vitro and in vivo.Methods: Mn-IONPs were prepared by the thermal decomposition of iron-eruciate and manganese-oleate complexes and were coated with 1,2-Distearoyl-sn-glycero-3-phosphoethanolamine-N-(methoxy[polyethylene glycol]-2000) (DSPE-PEG 2000). The physicochemical properties and cytotoxicity of the Mn-IONPs were fully characterized, followed by MRI in vitro and in vivo.Results: Ultrasmall 3 nm-sized nanoparticles were successfully prepared and were identified using transmission electron microscopy (TEM), high-resolution TEM, and X-ray diffraction. After coating with DSPE-PEG, the Mn-IONPs@PEG displayed excellent hydrophilicity and good biocompatibility. Due to the manganese-doping and PEG coating, the Mn-IONPs@PEG showed good relaxivity in vitro. Especially, the Mn-IONPs@PEG coated with DSPE-PEG following a mass ratio to Mn-IONPs of 1:20 showed harmonious longitudinal relaxivity (r1 = 7.1 mM−1s−1) and transversal relaxivity (r2 = 120.9 mM−1s−1), making it a better candidate for T1/T2 dual-contrast mMRI. After administrated via a caudal vein, the Mn-IONPs@PEG can induce significant enhancement in both T1-weighted and T2-weighted MR images and the time at 10 mins after injection was regarded as a suitable time for imaging because both the T1 and T2 enhancement were optimum at that time.Conclusion: The obtained Mn-IONPs@PEG exhibited good r1 and r2 and was a reasonable candidate for T1/T2 dual-contrast mMRI.Keywords: magnetic resonance imaging, manganese-doped iron oxide nanoparticles, T1/T2 dual-contrast, DSPE-PEG coating, high relaxivity